Elongation of teichuronic acid chains by a wall-membrane preparation from Micrococcus luteus. - Traxler, C I (1982)
A wall-plus-membrane preparation from Micrococcus luteus catalyzes the incorporation of [14C]glucose from UDP-[14C]glucose, into two fractions of teichuronic acid, which is the cell wall polysaccharide consisting of alternating residues of glucose and N-acetylmannosaminuronic acid (ManNAcUA). Membrane-associated teichuronic acid was extracted from the wall-membrane fraction of reaction mixtures by sodium dodecyl sulfate. The synthesis of membrane-associated teichuronic acid required UDP-glucose, UDP-ManNAcUA, and UDP-N-acetylglucosamine and was inhibited by tunicamycin. Glucose incorporated into wall-bound teichuronic acid remained in wall fragments after extraction with sodium dodecyl sulfate, and its incorporation required UDP-glucose and UDP-ManNAcUA (but not UDP-N-acetylglucosamine) and was insensitive to tunicamycin. Radioactive material incorporated into wall-bound teichuronic acid could be released by treatment with mild acid or by digestion with lysozyme, indicating that the wall-bound teichuronic acid was covalently linked to peptidoglycan. There were about 600 pmol of wall-bound teichuronic acid acceptor sites for glucose per mg of protein as measured in incorporation reaction mixtures lacking UDP-ManNAcUA. In the presence of both UDP-glucose and UDP-ManNAcUA, elongation of teichuronic acid acceptor sites occurred, with the addition of six to eight disaccharide units to each acceptor site.